Pedunculated perianal lipoma: a rare presentation - Deolekar, Sandesh; Shaikh, Tanveer Parvez; Ansari, Sharique; Mandhane, Nisha; Karandikar, Sangram; Lal, Vikash (International Journal of Research in Medical Sciences, 2017)
Lipomas are ubiquitous lesions. Most of the lipomas have a fibrous capsule and are divided into lobules by delicate septae. On gross examination and histological analysis, lipomas resemble mature fatty tissue.They are more compact on the cut surface than normal adipose tissue and the lobules are smaller on histological analysis. There is undoubtedly some physiologic difference between fat of lipoma and normal fat. Perianal lipomas are rare and may have deeper or interspincteric extensions. Preoperative evaluation to rule it out is a necessary part of the work up for any perianal lipoma. The case report is of a soft swelling on left side in the perianal region, which was investigated to rule out nature of the lesion or deeper and interspincteric extension. Case was managed by complete enucleation of the lipomatous swelling. Gross and microscopic examination of the surgical specimen revealed a perianal pedunculated lipoma.